Local and segmental motions of the mobile amorphous fraction in semi-crystalline polylactide crystallized under quiescent and flow-induced conditions. (22nd September 2017) - Monnier, Xavier; Chevalier, Laurence; Esposito, Antonella; Fernandez-Ballester, Lucia; Saiter, Allisson; Dargent, Eric
Abstract: The molecular dynamics of the constrained and unconstrained mobile amorphous fractions in semi-crystalline polylactide (PLA) was investigated in the presence of both flow-induced crystalline structures and spherulites by fast scanning calorimetry (FSC) through cooperativity and physical aging concepts. First, the shear rate conditions leading to flow-induced crystallization were characterized by examining the relaxation of shear-induced precursors. At a temperature of 150 °C, the critical relaxation time is so long that cooling down the sheared melt to the crystallization temperature does not affect significantly the precursors. Therefore, highly oriented structures develop. The arrangement of the crystalline fraction, either in flow-induced crystalline structures or spherulites, has no influence on the molecular dynamics of the mobile amorphous fraction, whereas the crystallinity degree was proved to play a significant role. Two kinds of molecular dynamics were distinguished, respectively associated to the α and secondary relaxations. The molecular dynamics related to the α relaxation of the mobile amorphous fraction was investigated in terms of cooperativity: a clear dependence on the coupling and the confinement by the crystals was observed, because a classic decrease of the cooperativity length was found when comparing amorphous to semi-crystalline PLA. On the contrary, the molecular dynamics related to the secondary relaxations of the mobile amorphous fraction was not modified by the presence of the crystals, as observed from close physical aging investigations below the glass transition. The different length-scale of the α and secondary relaxations seems to be the reason why the crystalline environment influences the macromolecular motions rather than the molecular or local motions. Graphical abstract: Highlights: Precursor relaxations are investigated for the first time in Polylactide. Complex crystalline structures are investigated at their typical length-scale. Molecular dynamics depend on crystallinity degree rather than crystalline morphology. Crystals hindered cooperativity motions related to α relaxation. Crystals play no role on the structural relaxation of mobile amorphous fraction.